How food made history - Higman, B. W., 1943- (Wiley-Blackwell, 2012)
"Covering 5,000 years of global history, How Food Made History traces the changing patterns of food production and consumption that have molded economic and social life and contributed fundamentally to the development of government and complex societies. Charts the changing technologies that have increased crop yields, enabled the industrial processing and preservation of food, and made transportation possible over great distances Considers social attitudes towards food, religious prohibitions, health and nutrition, and the politics of distribution Offers a fresh understanding of world history through the discussion of food"--